2015
DOI: 10.1016/j.pmedr.2015.01.004
|View full text |Cite
|
Sign up to set email alerts
|

School-travel by public transit: Rethinking active transportation

Abstract: BackgroundWalking and cycling to school is a source of physical activity (PA). Little is known about public transit use for travel to school and whether it is a physically active alternative to car use for those who live too far to walk.PurposeTo describe school-trip characteristics, including PA, across travel modes and to assess the association between PA with walk distance.MethodsHigh school students (13.3 ± 0.7 years, 37% female) from Downtown Vancouver wore accelerometers (GT3X+) and global positioning sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 24 publications
0
34
1
1
Order By: Relevance
“…We cleaned GPS data and generated activity spaces using methodology detailed elsewhere (Hirsch, Winters, et al, 2014; Voss, Winters, Frazer, & McKay, 2015; Voss, Winters, Frazer, & McKay, 2014). In short, GPS data were downloaded as .csv files (QStarz data viewer).…”
Section: Methodsmentioning
confidence: 99%
“…We cleaned GPS data and generated activity spaces using methodology detailed elsewhere (Hirsch, Winters, et al, 2014; Voss, Winters, Frazer, & McKay, 2015; Voss, Winters, Frazer, & McKay, 2014). In short, GPS data were downloaded as .csv files (QStarz data viewer).…”
Section: Methodsmentioning
confidence: 99%
“…Regular physical activity (PA) participation reduces the risk of disease, in addition to providing a multitude of benefits that help individuals sleep better, feel better, and perform daily tasks more easily [1]. These benefits can be achieved through a variety of PA modalities, and active travel (i.e., using self-propelled mediums, such as walking or cycling, some or all the way to a destination) can contribute as much as 30% towards meeting the recommended daily levels of PA for health [2,3]. A recent PA review [4] identified positive associations between active travel and health outcomes across 68 studies.…”
Section: Introductionmentioning
confidence: 99%
“…If walking to school is going to make a much greater contribution 249 to population MVPA in future, the prevalence, duration, and MVPA content of 250 walking to school must all be increased substantially. A discussion of policy and 251 strategy options and arguments for improving surveillance of active commuting to 252 school, and for increasing the prevalence and MVPA content of active commuting to 253 school, would go beyond the scope of the present study, but these issues are dealt with 254 elsewhere (31,42,49,51,52). Researchers and policymakers should also consider 255 whether focusing on domains of physical activity other than active commuting to 256 school might be more effective in the promotion of population MVPA (18).…”
mentioning
confidence: 97%